Clinical Characteristics and Outcomes of Dengue-infected Children Admitted to the Chiang Mai University Hospital During an Outbreak in 2008 - Sudjaritruk, Tavitiya; Oberdorfer, Peninnah (Biomedical Sciences and Clinical Medicine, 2024)
Objective To assess clinical characteristics, outcomes, and hospital costs of dengueinfected children, who were admitted to Chiang Mai University (CMU) Hospital during an outbreak in 2008. Methods All serologically confirmed dengue-infected children, who were admitted to CMU Hospital between January 1 and December 31, 2008 were reviewed retrospectively. Results A total of 130 children were included in the study. The median age was 12.2 years (interquartile range: 9.7-13.9). Seventy-eight children (60%) were males. Twenty children (15.4%) were classified as having dengue fever, 99 (76.1%) as having dengue hemorrhagic fever (DHF), and 11 (8.5%) as having dengue shock syndrome (DSS). The three most common presenting symptoms were acute fever (98.5%), nausea/vomiting (66.9%), and myalgia (55.4%). Hepatomegaly, hypotension, pleural effusion, and ascites were found more common in children with DDS than in those without it (p < 0.05). Children with DSS stayed significantly longer in hospital than those without it (7.1 vs. 3.3 days, p < 0.01). The mean hospital cost per admission was 10 times higher among children with DSS than those without it (US 181.9 vs. US 1,873.0, p < 0.001). The overall mortality rate was 1.5%. Conclusion Children with DSS showed higher clinical severity, longer hospital stay, and poorer outcomes than those without it. Prompt diagnosis and treatment definitely helps reduce morbidity, mortality and hospital costs.